Menggali Potensi Lokal Dengan Pengembangan UMKM Dan Peluang Desa Wisata Melalui KKN Tematik Di Desa Carangwulung, Wonosalam, Jombang - Aprilianti, Dennis; Huda, Syamsul; Utami, Anisa Fitria (Jurnal Pengabdian Pada Masyarakat Indonesia, 2023)
Carangwulung Village in the Wonosalam sub-district is developing its potential with the concept of a tourist village. This village offers a variety riches tourism potential. The problems experienced by Carangwulung residents are the lack of ability to develop local tourism potential and the lack of marketing of processed carangwulung products. In community serviceWhich carried out by students through the UPN "Veteran" East Java KKNT activities are intended to help maximize the potential of the area and it is hoped that the potential for tourism and umkm in Carangwulung village can compete with other, more advanced regions. The KKNT implementation uses direct observation, interviews, documentation, and literature study in obtaining data. As a result of these activities, KKNT students help the marketing process for tourism potential and MSMEs by holding "Pekan UMKM dan Layar Keliling" activities, assisting MSMEs marketing digitalization, and helping MSMEs actors in product photos.